How appropriateness and enjoyment of instructors' virtual backgrounds affect students' perceptions of learning - Kelly, Stephanie; Kim, Jihyun; Choi, Jae Hoon (Frontiers in Computer Science, 2024)
The present study examines how the appropriateness and enjoyableness of an instructor's virtual background affects student learning. The results of the study indicate that while students' perceptions of the appropriateness and their enjoyment of an instructor's virtual lecture background influence whether students believe that they learned, neither of these variables contribute to how much students are able to demonstrate they have actually learned. Furthermore, while female students perceive that they learned more, there is no difference in performance between male and female students.